The potential evapotranspiration of the different climatic regions Of Rio Grande do Sul - Mota, Fernando Silveira da; Goedert, Clara Oliveira (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to know the Potential Evapotranspiration of the diferrent climatic regions of Rio Grande do Sul, with the aim of determining the water disponibilities for agriculture in each region. The authors chcose Penman’s theory in order to have an precise idea about the amounts of Evapotranspiration in Rio Grande do Sul. An example of the calculus of the Evapotranspiration figures is presented. The annual Potential Evapotranspiration in Rio Grande do Sul, or in other words, the water needs for crops, presents the highest values in Missões, Depressão Central and Vale do Uruguai, and the lowest in Serra do Nordeste and Serra do Sudeste, and intermediate values in Campanha, Litoral and Planalto. Excetuating Porto Alegre which presents it's maximum Evapotranspiration in December, the other localities present it's maximum Evapotranspiration in January. For all localities the minimum is in June. The annual precipitation in the state boast Evapotranspiration; nevertheless, if we consider the seasonal distribuition of Evapotranspiration, which is much greater in summer than in winter, with intermediate values in spring and fall, plus the fact that the precipitation is the same in all seasons, we could see that there are times of water deficiency and excess. In Serra do Nordeste, Planalto, and center of Depressão Central normally there is no water deficiency, but water excess all the year around; nevertheless, the enormous variability of precipitation from year to year can cause drought in summer in the Planalto and center of Depressão Central regions, in some year. In Baixo Vale do Uruguai, Campanha, Litoral and east and west of Depressão Central, the Evapotranspiration is higher than precipitation from October to February. In Serra do Sudeste only in December the Evapotranspiration is higher than precipitation. In Missões December and January are normally dry. The regions of Campanha, Serra do Sudeste, Litoral, Vale do Uruguai, Missões and east and west of Depressão Central presents precipitation higher than Evapotranspiration in fall, winter and spring. About the drought intensity in the different regions the conclusions are: In the east of Depressão Central and Litoral we have long and intense drought; in Missões, short and intense drought, which occurs in January; in Serra Sudeste the drought is short and weak, occurring in December.